Do Ethical Values Work? A Quantitative Study of the Impact of Fair Trade Coffee on Consumer Behavior - Cailleba, Patrice (Journal of business ethics, 2010)
This study investigates the large French fair trade (FT) market and the importance of FT coffee within it, in an attempt to identify some general features of FT consumers. On the basis of 7,587 transactions, the authors also determine the impact of FT characteristics on customer behavior. The main result is somewhat surprising: FT coffee purchases seem to involve a temporary commitment as FT coffee consumers appear less loyal than traditional coffee consumers. The authors derive some business and academic implications.